2019
DOI: 10.1073/pnas.1905385116
|View full text |Cite
|
Sign up to set email alerts
|

Detecting community response to water quality violations using bottled water sales

Abstract: Drinking-water contaminants pose a risk to public health. When confronted with elevated levels of contaminants, individuals can take actions to reduce exposure. Yet, few studies address averting behavior due to impaired water, particularly in high-income countries. This is a problem of national interest, given that 9 million to 45 million people have been affected by water quality violations in each of the past 34 years. No national analysis has focused on the extent to which communities reduce exposure to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…First, we obtained the PET tonnage collected for recycling in each Minnesota county for 2009 to 2013. Second, we procured county-level data on sales of beverage bottled in PET from The Nielsen Company (US), LLC (a company that collects and maintains retailing data from the grocery, convenience, drugstore, and mass merchandising channels 20 ). Lastly, we gathered data from the U.S. Census Bureau for use as controls.…”
Section: Resultsmentioning
confidence: 99%
“…First, we obtained the PET tonnage collected for recycling in each Minnesota county for 2009 to 2013. Second, we procured county-level data on sales of beverage bottled in PET from The Nielsen Company (US), LLC (a company that collects and maintains retailing data from the grocery, convenience, drugstore, and mass merchandising channels 20 ). Lastly, we gathered data from the U.S. Census Bureau for use as controls.…”
Section: Resultsmentioning
confidence: 99%
“…Reports or news of water quality violations likely change people's perceptions of tap water safety and, resultingly, their avoidance behaviors (Jackson, 2017). Previous research has demonstrated that in counties reporting water quality violations, bottled water sales (a proxy of tap water avoidance) increased by 2.3% after the first Tier 1 violation, but that in counties with repeat violations, these same effects were not present (Allaire et al, 2019). News coverage dedicated to the Flint water crisis may have affected the decisions of parents elsewhere about the safety of their own tap water through the “availability heuristic” (Tversky & Kahneman, 1974).…”
Section: Discussionmentioning
confidence: 98%
“…These findings help unpack disparities of in-home tap water use, building upon analyses in which observations are aggregated across time or studies which used bottled water sales as a proxy of tap water avoidance (Allaire et al, 2019;Christensen et al, 2019;Patel et al, 2013;Rosinger et al, 2018;Zivin et al, 2011). Examining time trends allows for an evaluation of changes across critical demographic covariates in respect to large-scale events and magnitude of changes.…”
Section: 1029/2020wr027657mentioning
confidence: 96%
See 1 more Smart Citation
“…For example, during the highprofile violation of water quality standards in Flint, Michigan, when the maximum contaminant level for trihalomethanes was exceeded in December 2014, return to compliance was not achieved until 9 months later. 2 As customers wait for the supplier to fix the problem, either voluntarily or following legal action by the state or federal government, many purchase bottled water or filtration devices in order to avoid contaminants (Allaire et al 2019, Zivin et al 2011. Expenditure on avoidance methods has been used in the environmental economics literature to estimate the willingness to pay (WTP) for water quality improvements (Brouwer et al 2015, Brox et al 2003, Johnston and Thomassin 2010, Rodriguez-Tapia et al 2017 and similarly for air quality improvements (Freeman et al 2019).…”
Section: Introductionmentioning
confidence: 99%